(untitled) (Mugda Medical College Journal, 2025)
Klebsiella species have become increasingly prevalent in nosocomial infections, posing a significant challenge for developing and developed countries due to their resistance to commonly used antibiotics. This study assessed the changing antibiotic sensitivity patterns of Klebsiella pneumoniae isolates obtained from blood cultures in sepsis patients. This retrospective crosssectional study was conducted at the Department of Microbiology & Immunology, Ibn Sina Medical Centers in Dhaka, Bangladesh, from January 2021 to Dece mber 2023. One hundred and nineteen Klebsiella pneumonia samples were included in the study. All the Klebsiella pneumoniae were detected by the Automated Blood Culture System. Isolate identification and antibiotic susceptibility were performed using the Vitek 2 automated system. A few conventional biochemical tests were also performed for isolate identification. Our data revealed a consistently high sensitivity (100%) of Klebsiella pneumoniae isolates to Amikacin and Tigecycline, with Colistin demonstrating a sensitivity of 75%. In contrast, cefepime and amoxicillin showed 100% resistance, and resistance to azithromycin was 94%. A detailed yearly analysis highlighted increasing resistance trends, particularly notable in azithromycin, which went from 38% resistance in 2021 to 100% in 2023. Resistance of Klebsiella pneumoniae to commonly used antibiotics is a rising trend, which demands continuous surveillance strategies to address the emerging threat. Mugda Med Coll J. 2025; 8(1): 55-59